2019
DOI: 10.3389/fcvm.2019.00114
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function During Extracorporeal Membrane Oxygenation in Adult Patients

Abstract: Objective: Hemorrhagic and thromboembolic complications are common during support with extracorporeal membrane oxygenation (ECMO). As platelets play a pivotal role in hemostasis, we aimed to clarify how ECMO support affects platelet function. Methods: We included 33 adult patients undergoing ECMO support at a tertiary ECMO referral center at Aarhus University Hospital, Denmark. Blood samples were collected on the first morning following ECMO initiation, and subsequently every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…With this method less dependent on platelet count, they found that platelets demonstrated a reduced ability to become activated. The authors suggested that this could actually be consecutive to the vast activation of platelets in the ECMO circuit, related to the high shear stress, consistent with the increased surface expression of the activated fibrinogen receptor at rest, and a decreased expression of P-selectin, probably due to its shedding [15]. This was in agreement with previous data from our group in the setting of cardiopulmonary bypass in children [16].…”
Section: Blood Collection Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…With this method less dependent on platelet count, they found that platelets demonstrated a reduced ability to become activated. The authors suggested that this could actually be consecutive to the vast activation of platelets in the ECMO circuit, related to the high shear stress, consistent with the increased surface expression of the activated fibrinogen receptor at rest, and a decreased expression of P-selectin, probably due to its shedding [15]. This was in agreement with previous data from our group in the setting of cardiopulmonary bypass in children [16].…”
Section: Blood Collection Resultssupporting
confidence: 87%
“…Samples were then diluted in phosphate buffer saline (final blood dilution 1:44) and analyzed, the events being acquired on Navios (Beckman Coulter) or Lyric (Becton Dickinson) ( Figure 2). We evaluated (i) the type of anticoagulant solution, (ii) the delay between sampling and immunolabeling (15,60, and 150 min), (iii) the sample stability after immunolabeling (0 and 90 min), and (iv) the effect of strong vortex agitation (10 s at 3200 rpm), prior to immunolabeling. Figure 2.…”
Section: Pre-analytical Requirements-choice Of Anticoagulant Delay Bmentioning
confidence: 99%
“…Platelet counts were significantly lower in our study when bleeding had occurred despite our efforts to achieve target platelet levels above 80 thousand per μl. Platelet function as well as absolute counts play a considerable role in hemostasis [30]. Thrombocytopathy can also be an immediate cause of or contribute to ECMO-related hemorrhage [28].…”
Section: Plos Onementioning
confidence: 99%
“…This effect was also seen in a study in twenty patients on VV ECMO where platelet function was impaired prior to the ECMO initiation; ECMO led to a further impairment but after two days the values recovered to baseline [15]. In a study with both VV and VA ECMO patients it was shown that the platelet aggregation was not impaired when the results were interpreted considering the low platelet counts [16].…”
Section: Discussionmentioning
confidence: 64%